MAPPING THE CONVERGENCE TRENDS OF TELEVISION BROADCASTING MEDIA IN INDONESIA - Rizki Briandana; Edi Pribadi; Sarata Balaya (Bricolage : Jurnal Magister Ilmu Komunikasi, 2020)
This research will analyze the media convergence with the rapid development of the existing equipment in the broadcasting system of the television station in Indonesia. The digitalisation and advancement of communication and information technology have a tremendous impact on the emergence of a new paradigm and therefore, will also change the overall perspective of humans about various problems that occur around them. With the emergence of digital channels, the analogue media cannot support the existing system independently and require the integration of technologies in the discovery of new platforms. To analyze the paradigm shift of the television stations in Indonesia, this research uses the case study research method through interviews and observation data collection techniques. The research results show that technological and information changes in the broadcasting system in some technical parts of television media, i.e. the library system, post-production and broadcasting systems in the control room of the research. In responding to media convergence, the diversity of technologies involved in the processes of convergence, it makes the work more practical and efficient. Efficiency is very visible in the decent decrease of the production finance (cost) where works become competent with the integration of related units in the processes of convergence.